Gene regulation, alternative splicing, and posttranslational modification of troponin subunits in cardiac development and adaptation: a focused review - Sheng, Juan-Juan; Jin, Jian-Ping (Frontiers in Physiology, 2014)
Troponin plays a central role in regulating the contraction and relaxation of vertebrate striated muscles. This review focuses on the isoform gene regulation, alternative RNA splicing, and posttranslational modifications of troponin subunits in cardiac development and adaptation. Transcriptional and posttranscriptional regulations such as phosphorylation and proteolysis modifications, and structure-function relationships of troponin subunit proteins are summarized. The physiological and pathophysiological significances are discussed for impacts on cardiac muscle contractility, heart function, and adaptations in health and diseases.